2019
DOI: 10.3171/2019.6.spine19332
|View full text |Cite
|
Sign up to set email alerts
|

Total uncinectomy of the cervical spine with an osteotome: technical note and intraoperative video

Abstract: Total uncinate process resection or uncinectomy is often required in the setting of severe foraminal stenosis or cervical kyphosis correction. The proximity of the uncus to the vertebral artery, nerve root, and spinal cord makes this a challenging undertaking. Use of a high-speed burr or ultrasonic bone dissector can be associated with direct injury to the vertebral artery and thermal injury to the surrounding structures. The use of an osteotome is a safe and efficient method of uncinectomy. Here the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…It was in agreement with multiple studies that the indication of ACDF with UPR was CR with foraminal stenosis caused by osteophytes of hypertrophied UP. 17,18,27,28,32,33 In accordance with Sun B’s study, the width of the intervertebral foramen (wIVF) was found to be significantly associated with the improvement in post-operative outcomes. 17 The author reported that patients with pre-operative wIVF<3mm who underwent ACDF with UPR had significantly better improvement of post-operative clinical symptoms than those who underwent ACDF alone, which quantified the severity of foraminal stenosis in the indication.…”
Section: Discussionsupporting
confidence: 76%
“…It was in agreement with multiple studies that the indication of ACDF with UPR was CR with foraminal stenosis caused by osteophytes of hypertrophied UP. 17,18,27,28,32,33 In accordance with Sun B’s study, the width of the intervertebral foramen (wIVF) was found to be significantly associated with the improvement in post-operative outcomes. 17 The author reported that patients with pre-operative wIVF<3mm who underwent ACDF with UPR had significantly better improvement of post-operative clinical symptoms than those who underwent ACDF alone, which quantified the severity of foraminal stenosis in the indication.…”
Section: Discussionsupporting
confidence: 76%
“…[ 17 ] In deformity correction, the risk of arterial injury during the surgical treatment by the anterior, posterior, or combined approaches is increased. [ 18 19 20 21 ] This is compounded by the challenges posed by the tortuous course the vertebral artery may take due to abnormalities or variants to the normal anatomy associated with diseases and disorders of the craniovertebral junction. [ 22 ] Therefore, a preoperative angiogram is essential to have a meticulous understanding of the vascular anatomy of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Uncinatectomy has historically been a controversial procedure, with many advocating for avoidance due to the risk of vertebral artery and nerve root injury [7,8]. There have been several proposed techniques for safe uncinate removal, including extensive lateral exposure of the vertebral artery, use of an osteotome, and use of an ultrasonic aspirator [9,10]. In our experience, we have found that the passage of a freer dissector lateral to the uncinate border provides adequate protection of the neurovascular structures of the cervical foramen.…”
Section: Discussionmentioning
confidence: 99%